Recent thecideide brachiopods from a submarine cave in the Department of Mayotte (France), northern Mozambique Channel - Simon, Eric; Hiller, Norton; Logan, Alan; Theuerkauff, Dimitri; Mottequin, Bernard (Zootaxa, 2019)
For the first time large numbers of thecideide brachiopods have been collected from the Mozambique Channel, more particularly from the western part of the Comorian Island of Mayotte (France). The moderately diverse brachiopod fauna is from a submarine cave situated on the second barrier reef encircling this island, with three different genera being found: Thecidellina, Ospreyella and Minutella. The last genus is represented by M. cf. minuta (Cooper, 1981), which was first discovered around Madagascar. Ospreyella is represented by a new species (O. mayottensis sp. nov.) as is Thecidellina, which is represented by T. leipnitzae sp. nov. This species is markedly distinct from T. europa Logan et al., 2015 from Europa Island in the southern Mozambique Channel (1,200 km south of Mayotte), providing an example of allopatric speciation in an isolated cryptic habitat.